Preview-View-Review: Increasing Academic Access for Students with Severe Disabilities who are English Learners - Williamson, Dolores; Spies, Tracy; Higgins, Kyle; Sparks, Shannon (Journal of the American Academy of Special Education Professionals, 2022)
This study measured the effect of an evidence-based science curriculum delivered in both English and Spanish using the preview-view-review (PVR) strategy, on the science vocabulary and content knowledge acquired by students with moderate to severe intellectual disabilities who were learning English. The intervention was compared to the same research-based science curriculum delivered in English only. Using an adapted alternating treatments design, both the English and PVR interventions were delivered concurrently via different, but equally challenging lessons on cells (English only) and precipitation (PVR--English and Spanish). Results indicate that both the English-only and PVR (English and Spanish) interventions were effective in teaching science vocabulary words and pictures to English learners with ID. Although there was no measurable difference in the amount of student participation between the two conditions, there was a noticeable difference in the quality of discussion and participation by the students when taught in the PVR condition.